Machine learning and data analytics for predicting, managing, and monitoring disease - Roy, Manikant, 1989-; Gupta, Lovi Raj (Engineering Science Reference, 2022)
"This book provides the recent various theoretical frameworks, empirical research and application of advanced analytics methods for disease detection, pandemic management, disease prediction etc. using the data analysis methods and their usages for taking timely decisions for prevention of such spread of pandemic and how people in government, society and administer can use these insights for overall management"--